2020
DOI: 10.1016/j.ajem.2020.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Weakness and elevated creatinine kinase as the initial presentation of coronavirus disease 2019 (COVID-19)

Abstract: COVID-19 is a global public health emergency with more than one million positive cases across the globe. COVID-19 has a multifaceted presentation. We are herein to report two cases of SARS-CoV-2 induced rhabdomyolysis with an initial presentation of weakness and elevated creatinine kinase (CK). Both patients had no respiratory symptoms, they only complained of generalized weakness and were found to have elevated CK. Routine chest X-ray showed bilateral infiltrates in both cases and subsequently reverse-transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 13 publications
5
67
0
1
Order By: Relevance
“… Day 2: positive COVID-19 nasopharyngeal swab, ↑ LDH (497 U/L), CRP (37 mg/L), D-dimer (573 μg/L) & ferritin (2134 μg/L) NR NR Day 2: azithromycin, hydroxychloroquine, vancomycin & cefepime. Day 3: IV fluid, supportive care in ICU Favorable ( Chan et al, 2020 ) New York, USA 71, M On admission: intermittent leg twitching with tingling/numbness at the lateral upper thigh radiating down to the posterior mid-calf. No prior symptoms, fever on admission; Day 2: spike fever and AKI Day 3: tachypnea, tachycardia, AF with RVR, AKI & ARDS requiring intubation Admission: ↑ CK (1859 U/L), BUN (78 mg/dL), creatinine (3.6 mg/dL), troponin (0.249 ng/mL), LDH (538 U/L), CRP (18.8 mg/L), D-dimer (989 μg/L) & ferritin (1003 μg/L); normal CBC diff ; EKG: new AF, positive COVID-19 nasopharyngeal swab.…”
Section: Neurologic Manifestationsmentioning
confidence: 99%
“… Day 2: positive COVID-19 nasopharyngeal swab, ↑ LDH (497 U/L), CRP (37 mg/L), D-dimer (573 μg/L) & ferritin (2134 μg/L) NR NR Day 2: azithromycin, hydroxychloroquine, vancomycin & cefepime. Day 3: IV fluid, supportive care in ICU Favorable ( Chan et al, 2020 ) New York, USA 71, M On admission: intermittent leg twitching with tingling/numbness at the lateral upper thigh radiating down to the posterior mid-calf. No prior symptoms, fever on admission; Day 2: spike fever and AKI Day 3: tachypnea, tachycardia, AF with RVR, AKI & ARDS requiring intubation Admission: ↑ CK (1859 U/L), BUN (78 mg/dL), creatinine (3.6 mg/dL), troponin (0.249 ng/mL), LDH (538 U/L), CRP (18.8 mg/L), D-dimer (989 μg/L) & ferritin (1003 μg/L); normal CBC diff ; EKG: new AF, positive COVID-19 nasopharyngeal swab.…”
Section: Neurologic Manifestationsmentioning
confidence: 99%
“…On the one hand, it may be associated with heart injury in critically ill patients with COVID-19 [34]. On the other hand, this indicator was related to rhabdomyolysis [35][36].Several cases of rhabdomyolysis were reported in COVID-19 severe patients, with a marked increase of CK [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…SARS patients with RM had a high risk of renal failure and death (17)(18)(19). Regarding musculoskeletal complications, fatigue and myalgia were common symptoms (3,(25)(26)(27)(28), but COVID-19 complicated with RM has only rarely been reported so far (4)(5)(6)(7)(8)(9)(10)(11)(12). In fact, 138 patients with COVID-19, who were admitted to ICU, showed a tendency toward increased CK levels (27).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that COVID-19 RNA could enter the blood, accumulate in other organs, and result in damages (3). Recently, a few case reports described patients with COVID-19 that developed rhabdomyolysis (RM) during hospitalization (4)(5)(6)(7)(8)(9)(10)(11). Furthermore, an analysis of autopsies on 26 patients with COVID-19 revealed that pigmented casts associated with high serum CK levels could be found in 3 patients, which might represent RM (12).…”
Section: Introductionmentioning
confidence: 99%